Inhibition of bone resorption blunts osteoarthritis in mice with high bone remodelling. Issue 8 (4th June 2010) - Kadri, Abderrahim; Funck-Brentano, Thomas; Lin, Hilène; Ea, Hang-Korng; Hannouche, Didier; Marty, Caroline; Lioté, Frédéric; Geoffroy, Valérie; Cohen-Solal, Martine E
Abstract : Background: Osteoarthritis (OA) is characterised by cartilage degradation and bone lesions. Subchondral bone may be involved in the pathogenesis of cartilage matrix breakdown. Objective: To assess the role of bone remodelling in OA by studying the effect of bisphosphonate on OA development in mice with high bone remodelling. Methods: Mice overexpressing Runx2 (Runx2-Tg) under the control of collagen type I that displayed high bone remodelling were used. Joint instability was performed by partial medial meniscectomy to induce OA. Results: Six weeks after surgery, tibial cartilage of Runx2-Tg mice displayed an increased number of ADAMTS-4- and ADAMTS-5-expressing chondrocytes compared with controls (p<0.05). This increase was higher in Runx2-Tg mice than in wild-type mice, although their OA score did not differ (2.5±0.6 vs 2.4±0.2, P=NS). Pamidronate reduced the OA score in Runx2-Tg mice but not in wild-type littermates (1.2±0.5 vs 2.7±0.4; p<0.05) despite the reduction of bone resorption and of the expression of cartilage proteases in both genotypes. Conclusions: These findings support the hypothesis that the level of bone resorption influences cartilage metabolism and that inhibition might prevent the progression of OA. Targeting bone resorption might therefore provide an approach to the treatment of high bone resorbing forms of OA.